The Influence of UKI’s Tagline “UKI HEBAT” in Forming the Characters of UKI’s People to be “HEBAT” - Mesta Limbong; Yules Orlando Sianipar; Iosephine Sere G (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2022)
Through the tagline “UKI HEBAT”, the Head of the University and his staff hope that educators, staff, and other workers, as well as students, understand what the purpose of their work plan is and make the character of UKI people become “HEBAT, and the Universitas Kristen Indonesia (UKI) becomes better. better than other universities. The background of this research is to see the influence of the tagline through the Psycholinguistics-Cybernetic model in providing a